Diffusion of Indonesian dangdut music at the international level as an implementation of cosmopolitan aesthetics - Wicaksono, Zakaria Anton (Abdul Media Literasi, 2026)
This study examines the transnational diffusion of Indonesian dangdut music as a cultural phenomenon contributing to cosmopolitanism and international engagement. The intensification of globalization has progressively reconfigured the boundaries between local and global cultural production, positioning popular music as an aesthetic medium that articulates identity and facilitates cross-cultural exchange. Within this context, the increasing visibility of dangdut beyond Indonesia’s borders raises pertinent scholarly questions regarding the role of aesthetic practices in shaping soft power dynamics and intercultural acceptance. The research is conceptually anchored in multi-track diplomacy, which recognizes the interplay between state and non-state actors in transnational cultural dissemination. Methodologically, it employs a qualitative approach operationalizing Rogers’ theory of diffusion of innovations to analyze how cultural products evolve, adapt, and attain legitimacy within diverse social systems. This framework is integrated with the concept of cosmopolitan aesthetics, which foregrounds cultural hybridity and shared emotional experience as mechanisms fostering cross-cultural resonance. The central argument posits that the international diffusion of dangdut music exemplifies a cosmopolitan process wherein local cultural identities undergo recontextualization rather than erosion within global cultural flows. By conceptualizing dangdut as both an aesthetic expression and a diplomatic instrument, this study contributes to scholarly discourse on cultural diplomacy and offers an alternative paradigm for understanding how cultural practices may function as pathways toward engagement and harmony in contemporary international relations.